VD_FINDINFO HC / 2015 / 567 vom 30. Juni 2015 - VD Tribunal cantonal (2015)
MESURE PROVISIONNELLE, CONSTATATION DU DROIT ÉTRANGER, DROIT ÉTRANGER, RATTACHEMENT, OBLIGATION D'ENTRETIEN, CALCUL DU DÉLAI, DÉLAI | 179 CC, 16 LDIP, 62 LDIP, 8 CLaH 1973